MPLS-Based Micro-Mobility Architecture for 5G Vehicular Visible Light Communication Networks - Siddiqui, Sameera (Université d'Ottawa / University of Ottawa, 2020)
Future vehicular networks in the emerging era of 5G will be characterized by ubiquitous connectivity across heterogeneous networks (HetNets) while maintaining their required Quality of Service (QoS). Visible light communication (VLC) and mmWave are both promising candidates for use in last mile communication networks. However, selection of appropriate technology for vehicular systems is dependent on their performance in outdoor networks. Due to cell densification inherent in 5G communication networks, selection of an appropriate micro-mobility scheme that ensures seamless connectivity with QoS provision is critical. This thesis focuses on the investigation of these issues. VLC and mmWave are both evaluated for outdoor vehicular networks based on their propagation characteristics and attenuation due to adverse weather conditions. Based on comparative design analysis, we proposed the adoption of a dual-link, multi beam VVLC system for outdoor infrastructure vehicular communication networks. The design analysis was carried out using existing empirical and mathematical models. Compared to mmWave system, the proposed model was found a safer, power efficient and economically more viable solution. Multiprotocol Label Switching (MPLS) based micro-mobility management has the advantage of fast and efficient packet forwarding. This thesis proposes a hierarchical IntServ based MPLS architecture to overcome the limitations found in existing MPLS based micro-mobility schemes in terms of latency and explicit QoS support necessary for 5G vehicular communication networks. The survivability of communication networks is another critical issue. This thesis also proposes an improved fast re-routing scheme that decreases the path restoration delay compared to existing solutions proposed by IETF and found in the open literature. Our proposed schemes are evaluated through both mathematical and simulative analysis. The models were developed and simulated using the OPNET simulator to validate the analytical results. The results were also compared with other existing schemes to demonstrate the performance benefits of the proposed schemes.
Keywords: Vehicular Visible Light Communication; MPLS; 5G; Micro-mobility